Decision Support System for Determining Employee Bonus Using Analytical Hierarchy Process (AHP) and Simple Additive Weighting (SAW) Method At Spin Warriors Indonesia - michael vernannes marpaung; Aditiya Hermawan (Komunitas Dosen Indonesia, 2021)
Spin Warriors Indonesia has a number of employees who help in its development, employees are the main factor in the smooth running, progress and success of a company. Therefore, the provision of employee bonus allowances is carried out so that it affects all aspects of employee work. In general, the appraisal process for each employee takes a long time and is not necessarily accurate. All that happened because it used manual calculations. Based on the problems, a decision support system application was create which aims to simplify and perform a fast calculation process. This application uses the AHP and SAW methods which can provide accurate result because these methods have their respective advantages that complement each other. To test the system that was made then 7 users were distributed and filled out a questionnaire. Based od questionnaires that have been distributed and filled out by users, the results show that about 67.1% of respondents said they were quite satisfied with this application. Based on this data, it can be said that this application is useful for users to assist and facilitate companies in determining employee bonuses